The politics of national sovereignty in Hungary vs. EU Membership in Hungary - Szanto, Balazs (AEI Insights, 2021)
The paper takes a critical look at the National Consultation process in 2017 in Hungary to analyse the ongoing conflict between Budapest and Brussel. The Hungarian Government has been hostile to various EU policies arguing that they violate the sovereignty of Hungary. This paper seeks to refute this argument by showing that Hungary has the sovereignty to withdraw from the agreements, the obligations of which it refuses to honour. Rather, the Government is engaging in the politics of sovereignty, i.e. creating a sovereignty dispute in order to secure short-term political objectives, such as political survival. This dangerous trend can be observed in the populist politics of an increasing number of states, including the United Kingdom and the United States, and it presents a tangible threat to any order based on international law. The regimes in question use the politics of sovereignty in order to renege on their international obligations.